Implementasi Manajemen Risiko Dalam Perancangan Aplikasi Mobile Ensiklopedi Astronomi Islam Berbasis Android - Azza Ibraisama Ersyada (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2021)
Currently smartphone technology has become a very massive human need used by the wider community. Throughout the author's search on Google Play and the Apple Store, hundreds of software related to Islamic astronomy were found. It's just that those relating to the Islamic Astronomy Encyclopedia Application have not been found. With the existence of an information system about the Islamic Astronomical Encyclopedia on a smartphone device, it will certainly make it easier for users, especially astronomical scientists who need various information needed. Based on the results of the study, it can be stated that the presence of the Islamic Astronomy Encyclopedia Mobile Application is very useful for the development of Islamic astronomy studies.. The advantage of this application is that it uses open source so that the author can update the data at any time if data is found that is not yet available in the application. The next, so that the Islamic Astronomy Encyclopedia Application develops well and does not harm users who use risk management with various related SOP.